Efficacy of Pembrolizumab in the Treatment of Advanced Colorectal Cancer (Global Journal of Medical Research, 2024)
Colorectal cancer continues to be one of the leading causes of mortality among patients with neoplasia worldwide just behind to breast and prostate cancer The aim of this study was to evaluate the efficacy of pembrolizumab in advanced colorectal neoplasms to offer patients greater survival A search for scientific papers was carried out on the Pubmed and Lilacs platforms using the following descriptors colorectal cancer pembrolizumab and efficacy both in Portuguese and in English both being connected by the Boolean descriptor AND Thus a total of 33 articles were included after inclusion and exclusion criteria Despite the progress of studies these lines of treatment are limited to patients due to the high cost of medications